Dillenia pentagyna Roxb. (Dilleniaceae) in Central India: a Plea for its Conservation - Sikarwar, R. L. S.; Dubey, P. C.; Tiwari, Arjun Prasad (Indian Forester, 2016)
Dillenia pentagyna Roxb. (Dilleniaceae) is a moderate deciduous tree usually found in dry deciduous forests of Central India. It is a critically endangered species in Central India with very scant distribution. A detailed threat assessment cum ethnobotanical study was carried out by the authors during the year 2005-2009. The present paper provides data on its distribution, threat status and causes of depletion, ethnobotanical uses and conservation measures of the species.